Attitudes towards living organ donation: a cross-sectional survey study - Naibauer, Sydney; Branagan, William T.; Lehto, Stephanie; Reynolds, Nicole; Mikulich-Gilbertson, Susan; Page, Chloe E.; Davis, Rachel A. (Frontiers in Public Health, 2025)
ObjectiveOnly 18% of kidneys and livers transplanted in the United States come from living donors, and increasing rates of living organ donation could help decrease the critical organ deficit. Non-directed living donation is even less common, with only 1.4% of kidney and liver transplants coming from anonymous donors (1). This study aimed to determine which factors are considered more motivating and more discouraging to living organ donation, how characteristics of potential recipients affect willingness to consider living liver donation, and whether there are any associations related to a person’s willingness to consider non-directed living organ donation.MethodA cross-sectional survey was distributed in-person on a large medical campus, and participation was incentivized with the opportunity to spin a prize wheel. In addition to participant characteristics, the survey queried awareness of directed and non-directed living donation, whether or not the participant would consider directed donation and non-directed donation, motivating and discouraging factors to living donation, vignettes to assess willingness to donate to recipients with different characteristics, and an altruism personality inventory. An optional interpersonal reactivity index was included as well.ResultsThree hundred twenty-six participants scanned a QR code to take the survey. Most participants (299 of 318, 94%) were aware of living donation. Participants who said yes to considering non-directed living donation (67 of 305, 22%) had significantly higher altruism scores than those who said no (123 of 305, 40%). Willingness to consider living liver donation varied based on recipient characteristics, with participants reporting they would be more willing to donate to a recipient with an immune disorder over alcohol-related liver disease, an infant over an adult, a relative over a nonrelative, and a sibling with alcohol-related liver disease over a nonrelative with alcohol-related liver disease.ConclusionThe most motivating factors for considering living donation were having a child recipient, helping someone in need, high transplant center success rate, and helping a family member or friend. The most discouraging factors were uncompensated expenses, difficulty of surgery recovery, risk of surgery, and length of recovery. Participants were less willing to donate to adults, strangers, and recipients with alcohol-related liver disease.